Analysis of Boiler Start-Up Failure Risk with Grey FMEA and RCA Methods in Pt. PLTU Nagan Raya - Teuku AlKautsar; Arie Saputra (LPPM Politeknik Aceh Selatan, 2022)
PT. PLN (Persero) UPK Nagan Raya is a Steam Power Plant (PLTU) that uses coal as Boiler fuel to produce thermal energy. one of the initial stages of the Boiler is Startup as the basis for the start of Boiler operations. The purpose of this study is to analyze and avoid the risks that can make the operating system not run. Based on the research conducted, there are 8 risks that can cause failure. Based on the Grey FMEA method, the priority risk that occurs is that the FO fast shut-off cannot be O / C CCR with a value of 0.491 and also in the flexible joint line of the lower burner air there is a leak of 0.503. The result of the Root Cause Analysis method, the cause of the FO fast shut-off cannot be O / C CCR is the limited facilities and infrastructure for device maintenance which causes obstacles for workers so that the results worked on are not effective and efficient. Meanwhile, the risk that the flexible joint line air lower burner has a leak because it is not critical equipment only used at certain times so the check is neglected which makes the flexible joint leak. The solution that can be done is that as much as possible the operator must carry out routine maintenance/overhaul on the flexible joint so that there is no failure that can hinder the operation.